PARADOKS DETERMINISME DALAM FILM TENET (2020) SEBAGAI REFLEKSI KESADARAN MANUSIA AKAN WAKTU - Fatkhurridho, Farobi; Rusdiarti, Suma Riella (Paradigma: Jurnal Kajian Budaya, 2024)
Time is a complicated object of study because understanding time is closely related to periodization, history, and memory. Film is a medium for presenting manifestations of motion and time in visual products that can be captured by human senses. Tenet (2020) is a film that displays temporal dimensions in terms of both creative ideas and packaging through its cinematography and narrative structure. Tenet presents the idea of overlapping time consciousness of the past, present, and future. A revolving door machine in the film is used to signify the paradox of determinism or the condition of characters suffocated in a time loop. The form of aporia or deterministic indecision experienced by those characters reflects the dialogue of human consciousness on the temporal dimension. Tenet presents a debate on two human perspectives on or attitudes towards time, namely the modern and the postmodern, which are represented by the protagonist and Sator. From a more ideological standpoint, the film is full of ambivalences when presenting the dialogues and human attitudes towards time. This is in line with the perspective of metamodernism, namely a continuous pursue of the impossible. All of the actions taken by the protagonist and Sator will eventually prove to be impossible because they are trapped in an endless time loop